2019
DOI: 10.1038/s41598-019-56076-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification and ecology of alternative insect vectors of ‘Candidatus Phytoplasma solani’ to grapevine

Abstract: Bois noir, a disease of the grapevine yellows complex, is associated with ‘Candidatus Phytoplasma solani’ and transmitted to grapevines in open fields by the cixiids Hyalesthes obsoletus and Reptalus panzeri. In vine-growing areas where the population density of these vectors is low within the vineyard, the occurrence of bois noir implies the existence of alternative vectors. The aim of this study was to identify alternative vectors through screening of the Auchenorrhyncha community, phytoplasma typing by stam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
57
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 45 publications
9
57
0
2
Order By: Relevance
“…It is interesting to note that three insect species, recently identified as alternative vectors of CaPsol to grapevine (Phylaenus spumarius (L.), Psammotettix spp., and Dictyophara europaea (L.)), were found during the survey on Auchenorrhyncha carried out in the vineyard in Greve in Chianti. In detail, transmission trials demonstrated that such insects are able to vector to grapevine CaPsol carrying the sequence variant St5 [12]. Moreover, based on the preliminary results obtained in this study about the weeds, the absence of St5 and St18 CaPsol strains in the examined weeds can suggest that other insect vectors could be able to acquire and transmit CaPsol using the infected vines as phytoplasma source.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…It is interesting to note that three insect species, recently identified as alternative vectors of CaPsol to grapevine (Phylaenus spumarius (L.), Psammotettix spp., and Dictyophara europaea (L.)), were found during the survey on Auchenorrhyncha carried out in the vineyard in Greve in Chianti. In detail, transmission trials demonstrated that such insects are able to vector to grapevine CaPsol carrying the sequence variant St5 [12]. Moreover, based on the preliminary results obtained in this study about the weeds, the absence of St5 and St18 CaPsol strains in the examined weeds can suggest that other insect vectors could be able to acquire and transmit CaPsol using the infected vines as phytoplasma source.…”
Section: Discussionmentioning
confidence: 50%
“…In the last few years, numerous studies revealed that the BN epidemiology is more complex than previously postulated, reporting new relevant plant reservoirs (Vitex agnus-castus L. and Crepis foetida L.) for the known CaPsol vectors, and identifying some of the unknown alternative vectors [7,8,12]. Here, a new BN epidemiological pattern (grapevine-Rq-weeds) related to St10 CaPsol strains and milder symptoms is proposed.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Indeed, the positions of the infected grapevines confirmed a natural source of inoculum and the activity of potential vectors in spreading BN in this vineyard. Recently, Quaglino et al 54 identified new 'Ca. P. solani' vectors to grapevines, and they hypothized, in Northen Italian pedoclimatic conditions, the spreading of phytoplasma to vineyard boarders through H. obsoletus and its further transmission within the vineyard by the feeding activity of the alternative vectors.…”
Section: Discussionmentioning
confidence: 99%
“…Flavescence dorée phytoplasma is the causal agent of flavescence dorée and is one of the most important grapevine yellows diseases in the main viticultural areas of Europe. It has a highly speciesspecific vector, Scaphoideus titanus (Chuche and Thiéry, 2014;Quaglino et al, 2019).…”
Section: Synonyms: Not Applicable Eppo Code: Phyp64mentioning
confidence: 99%